2010
DOI: 10.11645/4.1.1469
|View full text |Cite
|
Sign up to set email alerts
|

Using online video to promote database searching skills:

Abstract: In recent years, online tutorials have become well-established tools for the delivery of information literacy training as information professionals continue to seek new and more effective ways to reach audiences. However, the rapid transience of technologies, and the ongoing need to maximise the efficiency of services, mean that the question of how best to exploit the online medium needs further exploration. This paper focuses on a project at the University of Surrey Library to develop a new approach to online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…The process of evaluating and assessing TEL interventions can be a challenging task. 8 It is important to use a mixed method approach to gather both quantitative and qualitative feedback which can be typically collected using techniques such as surveys and focus groups. ‘Use a variety of methods so that findings from one source can substantiate others’.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The process of evaluating and assessing TEL interventions can be a challenging task. 8 It is important to use a mixed method approach to gather both quantitative and qualitative feedback which can be typically collected using techniques such as surveys and focus groups. ‘Use a variety of methods so that findings from one source can substantiate others’.…”
Section: Methodsmentioning
confidence: 99%
“…In Gravett and Gill’s 8 analysis of their online video tutorial, they report that an anonymous comment form did not generate much feedback and that ‘ Student time constraints and reluctance to critique staff and/or resources ’, 8 could perhaps be considered as possible reason for low feedback volume. They therefore intended to use focus groups to supplement the data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due in part to the fact that more interactive tutorials require a larger time commitment (Alyse, Ergood, Padron, & Reber, 2012;Xiao, Pietraszewski, & Goodwin, 2004;Sherwill-Navarro & Layton, 2006). After spending six months developing one video tutorial, Gravett (2010) concluded that the project was "significantly more timeconsuming than expected" (p. 70), and expressed uncertainty over the project's future.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Screencasts have been used extensively in information literacy and computer science; for example, reference librarians use screencasts to show steps in how to find information in databases, searching tools, and writing citations (Betty, 2008;Carr & Ly, 2009;Gravett & Gill, 2010;Williams, 2010). Moreover, screencasts have been used in mathematics, material science, and engineering units.…”
Section: Literature Reviewmentioning
confidence: 99%